2021
DOI: 10.1038/s41467-021-22430-7
|View full text |Cite
|
Sign up to set email alerts
|

Input-specific modulation of murine nucleus accumbens differentially regulates hedonic feeding

Abstract: Hedonic feeding is driven by the “pleasure” derived from consuming palatable food and occurs in the absence of metabolic need. It plays a critical role in the excessive feeding that underlies obesity. Compared to other pathological motivated behaviors, little is known about the neural circuit mechanisms mediating excessive hedonic feeding. Here, we show that modulation of prefrontal cortex (PFC) and anterior paraventricular thalamus (aPVT) excitatory inputs to the nucleus accumbens (NAc), a key node of reward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…Neuronal connections between the midline thalamic nuclei or pBMA and the NAc are consistent with a previous retrograde study showing that retrograde AAV(retro)-tdTomato injection into the NAc of wild-type mice results in tdTomato expression in the midline thalamic nuclei and the BMA (Itoga et al, 2019). The NAc receives glutamatergic inputs from the PVT, and these inputs modulate hedonic feeding (Christoffel et al, 2021). Thus, NPY neurons in the NAc are directly regulated by excitatory input from PVT neurons and may modulate feeding behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Neuronal connections between the midline thalamic nuclei or pBMA and the NAc are consistent with a previous retrograde study showing that retrograde AAV(retro)-tdTomato injection into the NAc of wild-type mice results in tdTomato expression in the midline thalamic nuclei and the BMA (Itoga et al, 2019). The NAc receives glutamatergic inputs from the PVT, and these inputs modulate hedonic feeding (Christoffel et al, 2021). Thus, NPY neurons in the NAc are directly regulated by excitatory input from PVT neurons and may modulate feeding behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Based on emerging evidence in recent years, the PVT has been conceptualized to act as an emotional and motivational hub ( Choi et al, 2019 ; Choi and McNally, 2017 ; Hsu et al, 2014 ; Kirouac, 2015 ). The PVT contributes to conditioned fear ( Do-Monte et al, 2015 ; Penzo et al, 2015 ), conditioned sucrose ( Do-Monte et al, 2017 ; Labouèbe et al, 2016 ; Livneh et al, 2017 ), appetitive learning ( Otis et al, 2017 ), as well as drug seeking ( Giannotti et al, 2018 ; Hamlin et al, 2009 ; James et al, 2010 ; Kuhn et al, 2018 ; Matzeu and Martin-Fardon, 2018 ; Zhou et al, 2021 ) and food seeking ( Christoffel et al, 2021 ; Engelke et al, 2021 ), depending on specific PVT inputs and outputs ( Millan et al, 2017 ; Penzo and Gao, 2021 ). Moreover, PVT neurons encode multiple salient features of sensory stimuli, including aversive valence ( Li et al, 2011 ; Yasoshima et al, 2007 ; Zhu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…These neurons, controlled by glucose metabolism, are activated by hypoglycemia conditions and mediate sucrose-seeking (Labouèbe et al, 2016). A recent study also revealed the role of aPVT = > NAc in promoting high fat intake, and shed light on the potentiation of aPVT synapses with NAc D1-MSNs after repeated exposure to the high fat reward (Christoffel et al, 2021). Interestingly, aPVT = > NAc seemed to regulate the incentive motivational value of the diet rather than hunger itself, since inhibition of this circuit decreased the preference for a high fat All methods presented here directly targeted the thalamic neurons projecting to the NAc, either by retrograde transport of viral tools from the NAc to the thalamus (cell bodies), or by local manipulation of the thalamic projections in the NAc (terminals).…”
Section: Reward-seeking Behaviorsmentioning
confidence: 96%
“…paired chamber, as well as the breakpoint in a progressive ratio task (Christoffel et al, 2021). Several lines of evidence also suggest a key role of PVT circuitry in adaptive behavior, by influencing the decision to seek or avoid a reward (McGinty and Otis, 2020).…”
Section: Reward-seeking Behaviorsmentioning
confidence: 99%